Electronic structure and luminescence assets in white-light emitting Ca2V2O7, Sr2V2O7 and Ba2V2O7 pyro-vanadates: X-ray absorption spectroscopy investigations - Sharma, Aditya; Varshney, Mayora; Chae, Keun-Hwa; Won, Sung Ok (ROYAL SOC CHEMISTRY, 2018)
Ca2V2O7, Sr2V2O7, and Ba2V2O7 pyro-vanadates were synthesized using a modified chemical precipitation method and annealing. Detailed crystal structure, morphology, electronic structure and optical properties were investigated by XRD, UV-visible absorption, FTIR, Raman, FE-SEM, XANES, and photoluminescence spectroscopy. Rietveld refinement on the XRD patterns of Ca2V2O7, Sr2V2O7, and Ba2V2O7 has confirmed the triclinic structure (space group; P (1) over bar (2)) of the pyro-vanadates. The band gap energy of Ca2V2O7, Sr2V2O7, and Ba2V2O7 is estimated to be similar to 2.67 eV, similar to 2.97 eV and similar to 3.09 eV, respectively. XANES spectra at the Ca L-edge, Sr K-edge and Ba L-edge have confirmed the Ca2+, Sr2+ and Ba2+ ions in the Ca2V2O7, Sr2V2O7 and Ba2V2O7 compounds, respectively. V K-edge XANES spectra have strengthened the presence of sub-pentavalent V ions in all of the pyro-vanadates. O K-edge XANES spectra of Ca2V2O7, Sr2V2O7 and Ba2V2O7 have shown dominating tetrahedral symmetry of the V ions which is also corroborated with the V K-edge XANES. Broad-band emission spectra, ranging from 400 nm to 700 nm, have been observed from the charge-transfer transitions of VO4 tetrahedra. T-3(1)->(1)A(1) and T-3(2)->(1)A(1) transitions, from the VO4 tetrahedra, have provided two distinct emission peaks from the compounds which exhibit a red-shift with the decreasing ionic-radii of alkali-earth metal ions. The mixed compounds, with equal weight proportions, have shown remarkable emission characteristics towards the realization of rare-earth element free white-light-emitting devices.
Keywords: MICROWAVE DIELECTRIC-PROPERTIES; MECHANISTIC INSIGHTS; FILMS; PHOTOLUMINESCENCE; PHOSPHORS; NANOPARTICLES; FABRICATION; CERAMICS; XANES; EXAFS